PENGARUH KONSEP KEHARMONISAN EKOLOGIS DALAM TEORI ARSITEKTUR TERHADAP PENGEMBANGAN DESAIN BANGUNAN HIJAU: STUDI KASUS KARYA FRANK LLOYD WRIGHT - Inriyani Inriyani; Zulkifli Anshari (Yayasan Nusantara Hasana Berdikari, 2026)
The concept of ecological harmony constitutes a fundamental basis in the development of sustainable architecture. Long before the formal emergence of green building principles, Frank Lloyd Wright had implemented ecological ideas through his organic architecture approach. This study aims to examine the influence of ecological harmony concepts in architectural theory on the development of green building design through a case study of Frank Lloyd Wright’s works. A qualitative-descriptive method with a case study approach was applied to three major works: Fallingwater, Taliesin, and the Usonian houses. The analysis employed twelve ecological harmony indicators (I1–I12), covering site integration, landscape, climate response, material use, spatial organization, passive design strategies, indoor environmental comfort, and ecological impact. The results demonstrate that Wright’s works consistently embody ecological harmony principles aligned with contemporary green building concepts. These findings confirm the continued relevance of Wright’s organic architecture theory as a conceptual foundation for sustainable architectural design today.